The Reconstruction of Qibla Burial Practice: An Islamic Law and Human Rights Perspective - Fatimah, Fatimah; Taman, Badrun; Baxadirovna, Bazarova Dildora (Universitas Negeri Surabaya, 2025)
The Indonesian state has an obligation to protect the basic rights of its citizens, including the right to be buried properly according to their religion and beliefs. This research aims to analyze the reconstruction of regulations on burial practices facing the Qibla for Muslims from the perspective of Islamic law and human rights. This study is a normative legal research with a conceptual and legislative approach. The research findings emphasize that the state plays a role in ensuring that Muslims can fulfill their religious obligation regarding graves facing the Qibla, which can be realized through the provision of appropriate burial facilities, education, and non-discriminatory regulations. The local government strives to achieve this by measuring and establishing the direction of the qibla at Public Cemeteries (TPU), enhancing socialization, and conducting regular calibration and evaluation. Therefore, the state needs to reconstruct the regulations for graves facing the Qibla, in accordance with Islamic law and positive law, through the revision of Government Regulation No. 9 of 1987, which includes standardizing the direction of the Qibla, educating burial officers, optimizing land use, and clarifying the role of local governments. With comprehensive regulations, the state can guarantee human rights, particularly the freedom of religion and belief. Keywords: Religious Rights, Islamic Law, Islamic Burial, Role of the State.